Trolled - Coville, Bruce (Coville, Bruce. Enchanted files, 2017)
Ned Thump is a seven-foot troll who is made fun of for his love of words so he escapes from the Enchanted Realm to the human world and secretly becomes a night watchman at Grand Central Terminal.